AUDIOMETRIC PROFILE AND CLINICAL CHARACTERISTICS OF HEARING IMPAIRMENT IN ADULTS AT NANGARHAR UNIVERSITY TEACHING HOSPITAL - Abdul Azeem Rasouli; Mohammad Azim Azimee; Fahima Azeem (Interdisciplinary Approaches to Medicine)
Hearing loss (HL) is defined as a partial or total inability to perceive sounds in one or both ears, varying from mild to profound levels. This study aimed to determine the audiometric profile and clinical features of hearing loss among individuals who attended the Ear, Nose, and Throat Department at Nangarhar University Teaching Hospital (NUTH). This cross-sectional study involved 93 patients over a 15-month duration, from September 2023 to the end of November 2024. Adult patients aged 18 and older, presenting symptoms of hearing loss, were included in the study. Participants were divided into three age categories: 18-39 years (11.8%), 40-59 years (34.4%), and 60 years and older (53.8%). Males were 58.06%, and females were 41.93%. Individuals aged 60 and older showed the highest frequency of hearing loss, mostly with sensorineural hearing loss (40.86%), mixed hearing loss (8.60%), and conductive hearing loss (4.30%). Regarding laterality, 25.8% of patients had unilateral impairments, while 74.19% experienced bilateral hearing loss. Diabetes mellitus was present in 30.1% of the population, while hypertension affected 35.48%. Regarding the severity of hearing loss, 30.10% reported mild hearing loss (26-40 dB), whereas moderate hearing loss (41-55 dB) represented 32.25%. Profound hearing loss (91 dB or greater) was uncommon, occurring in 2.15% of cases. Tinnitus was reported by 37.63%, while vertigo was observed in 13.97%, predominantly among individuals with sensorineural hearing loss. The research revealed that hearing loss is prevalent among individuals over 60 years of age, primarily of sensory-neural origin, frequently associated with tinnitus and vertigo. Bilateral hearing loss was more prevalent than unilateral hearing loss, particularly in individuals with comorbidities such as diabetes and hypertension.